The shape-shifting figure of Odiyan in select works: A new venture - V. G., Jisha; Gill, J. Chriso Ricky (Edelweiss Applied Science and Technology, 2024)
As far as Indian soil is concerned, there is no shortage of myths and mythical figures who can always create different feelings such as devotion, love, fear, etc. in people’s minds. Indeed, the formation of culture in each place is deeply influenced and adhered by these myths and figures. Mythical tales and figures are often selected for fictional as well as film narratives which are mostly used by the concerned regional writers who bring them forth as wonderful works. One such fabulous figure is Odiyan who is very popular collating with the other mythical figures in Kerala mythology. The age of Odiyans reminds dark innings and the people from Kerala advocate that Odiyans are real, not a myth because they are a group of people allied to the most subverted community the Paraya. It has been claimed that Odiyans existed during the 1950s and 60s at that time the caste system was at its zenith in Kerala. As the saying goes that Odiyans performed a kind of black magic that is known as Odi which was performed by most of the downtrodden people but commonly effectuated by the Paraya Community as a defence and for survival. They were commonly known as Odiyans and they were also capable for shapeshifting. There are not so many literary works that are articulated on Odiyans in the regional Malayalam literature then not to speak of English literature. Arundhati Roy and Anita Nair became famous as regional writers in English from Kerala who were born and brought up in the same era when Odiyans were believed to have existed. Roy is from Kottayam and Nair is from Palakkad and both the districts were popular with Odiyans. The hints about the Odiyans can be read as indirectly from Roy’s The God of Small Things and directly from Anita Nair’s The Better Man. The present study relocates how the Odiyan myth is beautifully incorporated in both novels.